2013
DOI: 10.1080/01411926.2011.627420
|View full text |Cite
|
Sign up to set email alerts
|

Helping counts: predicting children's intentions to disclose being bullied to teachers from prior social support experiences

Abstract: Despite possible negative effects, many children do not tell their teachers when they have been bullied. This study examined junior school pupils' (N = 294) reports of instrumental, emotional and validation social support received after disclosing being bullied to teachers, and associations with intentions to disclose in the future. Overall, participants reported receiving modest to high levels of social support. The three social support variables accounted for a significant proportion (16.3%) of the variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…In line with past research, gender, social preference and peer popularity were significant predictors of defending (Caravita et al, 2009;Caravita et al, 2012;Pöyhönen et al, 2010;Salmivalli et al, 1996). The effect of teacher support was marginally significant, which supports the notion that this so far understudied variable deserves greater research attention (Boulton et al, 2013). The result of our main interest-the link found between moral motivation and defending-showed that the previously documented association between moral motivation and prosocial behaviour (Gasser & Keller, 2009;Malti, Gummerum, et al, 2009b) holds for defending, even when a broader range of predictors are taken into account.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with past research, gender, social preference and peer popularity were significant predictors of defending (Caravita et al, 2009;Caravita et al, 2012;Pöyhönen et al, 2010;Salmivalli et al, 1996). The effect of teacher support was marginally significant, which supports the notion that this so far understudied variable deserves greater research attention (Boulton et al, 2013). The result of our main interest-the link found between moral motivation and defending-showed that the previously documented association between moral motivation and prosocial behaviour (Gasser & Keller, 2009;Malti, Gummerum, et al, 2009b) holds for defending, even when a broader range of predictors are taken into account.…”
Section: Discussionsupporting
confidence: 88%
“…While gender and peer status are proved correlates of defending (Caravita, Di Blasio, & Salmivalli, 2009;Caravita, Gini, & Pozzoli, 2012;Pöyhönen, Juvonen, & Salmivalli, 2010;Salmivalli et al, 1996), teacher support (i.e., social support provided by teacher/s) was added mainly for theoretical reasons. We assume that teacher support may encourage defending, because students' willingness to disclose bullying to teachers positively associates with teacher support (Boulton et al, 2013) and students are more likely to decide in favour of defending, when they view the environment as welcoming positive change (Feigenberg et al, 2008).…”
mentioning
confidence: 99%
“…These interventions may be interpreted by student victims as blaming them or suggesting that they did something to deserve this form of abuse. These responses may promote continued victimization [21,22,23,24,25,30,64,65,66,67]. They may also be interpreted by the victim in a way that they need to solve these problems on their own without any adult assistance.…”
Section: Discussionmentioning
confidence: 99%
“…All school personnel can and should play a critical role in the reduction and elimination of bullying episodes [19,20,21,22,23,24]. Regrettably, teachers, preservice teachers and other school personnel have difficulty in identifying bullying due to a lack of training, time and resources [25,26,27,28,29,30]. The negative effects of bullying (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Resources may include training or professional staff that come with anti-bullying programs that are more likely to be present in elementary and middle school contexts. Middle school students are more likely to disclose bullying events to teachers when they have received support in the past (Boulton et al 2013), and this pattern may extend to high school students. High school teachers may also be less likely to investigate possible bullying incidents if they feel that high school students have a greater capacity for dealing with the events on their own.…”
Section: Relationships With Teachersmentioning
confidence: 99%